IDENTITAS SEORANG KATEKIS PROFESIONAL DEWASA INI - Albert I Ketut Deni Wijaya (Lembaga Penelitian STKIP Widya Yuwana, 2019)
The work of catechesis as a work of developing faith in Christ, of course requires a diverse range of catechists. The types of catechists can be distinguished by time to work, education, and various catechetical needs. This paper aims to explain the identity of a catechist. The discussion of catechist identity includes catechism, catechist spirituality, catechism in the mission of the Church and professional climate, the Holy Spirit in the mission of catechists.Catechists are required to continually develop themselves. The development covers aspects of spirituality, knowledge and skills.